Dataset - Self-Heating of Biochar during Postproduction Storage by O₂ Chemisorption at Low Temperatures - Umeki, Kentaro (Luleå University of Technology, 2022)
Biochar is attracting attention as an alternative carbon/fuel source to coal in the process industry and energy sector. However, it is prone to self-heating and often leads to spontaneous ignition and thermal runaway during storage, resulting in production loss and health risks. This study investigates biochar self-heating upon its contact with O₂ at low temperatures, i.e., 50–300 °C. First, kinetic parameters of O₂ adsorption and CO₂ release were measured in a thermogravimetric analyzer using biochar produced from a pilot-scale pyrolysis process. Then, specific heat capacity and heat of reactions were measured in a differential scanning calorimeter. Finally, a one-dimensional transient model was developed to simulate self-heating in containers and gain insight into the influences of major parameters. The model showed a good agreement with experimental measurement in a closed metal container. It was observed that char temperature slowly increased from the initial temperature due to heat released during O₂ adsorption. Thermal runaway, i.e., self-ignition, was observed in some cases even at the initial biochar temperature of ca. 200 °C. However, if O₂ is not permeable through the container materials, the temperature starts decreasing after the consumption of O₂ in the container. The simulation model was also applied to examine important factors related to self-heating. The results suggested that self-heating can be somewhat mitigated by decreasing the void fraction, reducing storage volume, and lowering the initial char temperature. This study demonstrated a robust way to estimate the cooling demands required in the biochar production process.

The dataset was originally published in DiVA and moved to SND in 2024.

Biochar is attracting attention as an alternative carbon/fuel source to coal in the process industry and energy sector. However, it is prone to self-heating and often leads to spontaneous ignition and thermal runaway during storage, resulting in production loss and health risks. This study investigates biochar self-heating upon its contact with O₂ at low temperatures, i.e., 50–300 °C. First, kinetic parameters of O₂ adsorption and CO₂ release were measured in a thermogravimetric analyzer using biochar produced from a pilot-scale pyrolysis process. Then, specific heat capacity and heat of reactions were measured in a differential scanning calorimeter. Finally, a one-dimensional transient model was developed to simulate self-heating in containers and gain insight into the influences of major parameters. The model showed a good agreement with experimental measurement in a closed metal container. It was observed that char temperature slowly increased from the initial temperature due to heat released during O₂ adsorption. Thermal runaway, i.e., self-ignition, was observed in some cases even at the initial biochar temperature of ca. 200 °C. However, if O₂ is not permeable through the container materials, the temperature starts decreasing after the consumption of O₂ in the container. The simulation model was also applied to examine important factors related to self-heating. The results suggested that self-heating can be somewhat mitigated by decreasing the void fraction, reducing storage volume, and lowering the initial char temperature. This study demonstrated a robust way to estimate the cooling demands required in the biochar production process.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Dataset - Self-Heating of Biochar during Postproduction Storage by O₂ Chemisorption at Low Temperatures
Keywords: O2 chemisorption; O2 chemisorption; thermal runaway; thermal runaway; packed-bed simulation; packed-bed simulation; Energy Engineering; Energy Engineering; biochar; biochar; self-heating; self-heating; large-scale storages; large-scale storages; Energy Engineering; Energiteknik